2018
DOI: 10.1002/mp.12800
|View full text |Cite
|
Sign up to set email alerts
|

Incident learning in radiation oncology: A review

Abstract: Incident learning is a key component for maintaining safety and quality in healthcare. Its use is well established and supported by professional society recommendations, regulations and accreditation, and objective evidence. There is an active interest in incident learning systems (ILS) in radiation oncology, with over 40 publications since 2010. This article is intended as a comprehensive topic review of ILS in radiation oncology, including history and summary of existing literature, nomenclature and categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 141 publications
2
51
0
3
Order By: Relevance
“…Incident learning systems have been proven to be a valuable source of information and should be used for process improvement. 48 The tracking of incidents during the initial plan check is strongly encouraged to facilitate improvement in both the planning process and the plan check process.…”
Section: A1 Practice Recommendations For Photon/ Electron Ebrt Inmentioning
confidence: 99%
“…Incident learning systems have been proven to be a valuable source of information and should be used for process improvement. 48 The tracking of incidents during the initial plan check is strongly encouraged to facilitate improvement in both the planning process and the plan check process.…”
Section: A1 Practice Recommendations For Photon/ Electron Ebrt Inmentioning
confidence: 99%
“…ILS have been implemented in many organisations globally to improve safety in RO delivery. The development and use of ILS is supported by professional society recommendations, industry regulations, accreditation and objective evidence [8]. These include ASTRO's ''Target Safely" campaign [9], The European society for radiotherapy and oncology's (ESTRO) Radiation Oncology Safety Education Information System (ROSEIS) [10], a voluntary web based reporting system designed for individual clinic use as well as facilitating information exchange between clinics.…”
Section: Introductionmentioning
confidence: 99%
“…The ILS performance was analysed over an initial three year study period (2004)(2005)(2006)(2007) and the results indicated a reduction in error rate, both near miss and actual error [17]. However, determining whether the system specifically improves safety remains uncertain since reporting rates are influenced by other variables such as the introduction of new technology and changes in reporting culture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such a system can require substantial effort. 7 However, the bulk of this effort need not be shouldered by the medical physicist nor, arguably, should it be. The effort should be distributed amongst many professional staff and trainees.…”
Section: B | Resources and Structurementioning
confidence: 99%